Hubungan Pengetahuan dengan Perilaku Merokok Pada Siswa SMK Negeri Tanjungsari Lampung Selatan - Zainul Umari; Nopi Sani; Tusy Triwahyuni; Rina Kriswiastiny (Jurnal Ilmiah Kesehatan Sandi Husada, 2020)
Smoking is one of the activities that still carried out by individuals in all ages ranging from children to adults. Smoking offers the possibility for an ex-smoker to become a smoker again or for those who have never tried smoking to get interested in trying it. They always have a reason to smoke. The prevalence of active smokers in Indonesia increases rapidly. If the government does not wide-awake with more effective policies, the number of smokers in Indonesia is estimated will be increased by 90 million people in 2025